Environment-Growth Nexus: Revisiting Prosperity and Challenges Associated with Foreign Direct Investment - Arshad, Iqra; Azhar Khalil, Muhammad (NIDA Development Journal, 2022)
In this study, we develop a model to investigate the interactions between foreign direct investment (FDI), carbon emission (CO2), fixed capital accumulation (FCA), and economic growth by analyzing the sample from one of the emerging economies in Asia i.e., Pakistan during 1970 – 2017. In particular, the study examines the impact of FDI on both economic growth and environmental degradation. Using Ordinary Least Square and Johansen Juselius Co-integration approach, we observed that all the explanatory variables (i.e., FDI, CO2, and FCA) are positively related to the gross domestic product (GDP). Further analysis confirmed the widely accepted belief that FDI positively and significantly contributes to economic growth. However, such economic prosperity is generated at the cost of the environment, as the results show that FDI fosters the current level of CO2 which in turn poses a substantial challenge to the environmental quality. We offer a set of policies that policymakers should consider in Pakistan’s environmental protection policy plan to combat environmental degradation and emissions.